The Effect of Accounting Conservatism and Good Corporate Governance on Equity Valuation - Nurul Fuada (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
This study aims to examine and analyze the effect of accounting conservatism and good corporate governance (managerial ownership and independent commissioners) on corporate equity valuation in telecommunications companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach. The number of samples obtained was 30 using the purposive sampling method, with the criteria that the sample was listed on the Indonesia Stock Exchange (IDX), financial statement data were available consecutively and the type of company was a telecommunications company. Secondary data was collected using the method of documentation in the form of financial statements. With the help of SPSS for windows software, all data in this study were analyzed using a data analysis stage consisting of classical assumption tests (normality test, multicollinearity test, and heteroscedasticity test), hypothesis testing (multiple linear regression equation test, coefficient of determination test, and statistical t-test). The results show that accounting conservatism and independent commissioners positively and significantly affect the company's equity valuation. In contrast, managerial ownership has a negative and significant impact on the company's equity valuation of telecommunications companies listed on the Indonesia Stock Exchange.